Sestrin2, a Regulator of Thermogenesis and Mitohormesis in Brown Adipose Tissue - Ro, Seung-Hyun; Semple, Ian; Ho, Allison; Park, Hwan-Woo; Lee, Jun Hee (Frontiers in Endocrinology, 2015)
Sestrin2 is a stress-inducible protein that functions as an antioxidant and inhibitor of mTOR complex 1. In a recent study, we found that Sestrin2 overexpression in brown adipocytes interfered with normal metabolism by reducing mitochondrial respiration through the suppression of uncoupling protein 1 (UCP1) expression. The metabolic effects of Sestrin2 in brown adipocytes were dependent on its antioxidant activity, and chemical antioxidants produced similar effects in inhibiting UCP1-dependent thermogenesis. These observations suggest that low levels of ROS in brown adipocytes can actually be beneficial and necessary for proper metabolic homeostasis. In addition, considering that Sestrins are ROS-inducible and perform ROS-detoxifying as well as other metabolism-controlling functions, they are potential regulators of mitohormesis. This is a concept in which overall beneficial effects result from low-level oxidative stress stimuli, such as the ones induced by caloric restriction or physical exercise. In this perspective, we incorporate our recent insight obtained from the Sestrin2 study towards a better understanding of the relationship between ROS, Sestrin2 and mitochondrial metabolism in the context of brown adipocyte physiology.